MORTALITY TRENDS IN THE REPUBLIC OF SRPSKA IN THE 21ST CENTURY (2001-2022) - Pašalić, Stevo; Đurić, Aleksandar (ACADEMIC REVIEW, 2023)
Negative demographic trends in Republic of Srpska (negative natural increase, negative migration balance, aging) have an increasingly significant impact on the socio-economic development Republic of Srpska. At the beginning of the 21st century, the long-term decrease in the number of births and increase in the number of deaths were recognized as destabilizing factors of demographic development. The intensification of population emigration to EU countries and other countries of the world (USA; Canada, Australia) is of particular concern. Mortality in Republika Srpska was influenced by various socio-economic, demographic and epidemiological factors. The main goal of this paper is to analyze the changes in mortality indicators within the framework of contemporary trends in population movements in the Republic of Srpska. The results of the research show that certain changes (positive and negative) related to mortality were recorded in the Republic of Srpska (increase in life expectancy at birth, decrease in infant mortality, and some trends that are not favorable, especially those related to the causes of mortality. Although there was until the decrease in the share of deaths from some diseases, a significant increase in the number of deaths from certain diseases (Covid-19) was recorded, which can attributed to an unhealthy lifestyle and various behavioral factors. Key words: Мortality, mortality by cause, life expectancy at birth.